THE INFLUENCE OF REMAXOL ON HOMOCYSTEINE METABOLISM IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - V. M. Zhenilo; Z. T. Astakhova; A. Z. Avsaragova; M. V. Zhenilo; A. J. Razin (Медицинский вестник Юга России, 2015)
Purpose: study of Remaxol and Cytoflavin influence on homocysteine metabolism and creation of a method for correction of hyperhomocysteinemia development.Materials and methods: we examined 58 patients with diagnosed acute myocardial infarction with ST segment elevation complicated with acute heart failure according to Killip classification (class II-III). The patients were subdivided in two groups: the first group received traditional intensive therapy while the second group additionally received Remaxol and Cytoflavin. We studied the condition of homocysteine metabolism in connection with various types of intensive care.Results: we established that the first group even after seven days had homocysteine level consistently higher than in the control group while the second group by the seventh day demonstrated complete normalization of this essential ferment defining the development of endothelial dysfunction.Summary: intensive therapy of acute myocardial infarction including Cytoflavin and Remaxol decreases the intensity of pathochemical reactions: development of oxidative stress, and completely normalizes homocysteine metabolism.